ESRA19-0175 The analgesic efficacy of pecs blocks after breast surgery: a systematic review, meta-analysis and trial sequential analysis. (30th August 2019) - Grape, S; Jaunin, E; El-Boghdadly, K; Albrecht, E
Abstract : Background and aims: The pectoral nerves (PECS) blocks were developed to reduce pain after breast surgery. There are conflicting published data on the efficacy of these regional anaesthetic techniques. We therefore undertook a systematic review and meta-analysis to determine whether PECS blocks provide effective postoperative analgesia, when compared with no regional technique, in patients having breast surgery. Methods: We adhered to the PRISMA statement guidelines and searched the EMBASE and PUBMED electronic databases, among others, up to February 1, 2019. Randomised controlled trials comparing any PECS blocks with no block or sham injection were included. Meta-analyses were performed employing a random effects model. the primary outcome was rest pain score (0–10) at 2 postoperative hours which was analyzed according to the anaesthetic maintenance strategy (volatile agent vs propofol). Secondary outcomes included rest pain scores and cumulative intravenous morphine equivalents consumption (mg) at 12 and 24 postoperative hours, along with rate of PONV and pruritus at 24 postoperative hours. Results: Fourteen trials including 908 patients were identified. table 1 presents the trial characteristics. Rest pain scores at 2 postoperative hours were decreased in the PECS block group, with a mean difference (95%CI) of -1.5 (-2.1 to -0.1); I 2=93%; p<0.001, without differences between anaesthetic maintenance subgroups (p=0.62; figure 1). Similarly, all pain-related outcomes were significantly improved in the PECS block group (table 2 ). Conclusions: PECS blocks provide effective postoperative analgesia after breast surgery when compared with no regional technique.